ISOLASI DAN IDENTIFIKASI SENYAWA ANTIMAKAN DARI BATANG TUMBUHAN BROTOWALI (Tinospora tuberculata BEUMEE.) - I M. Sukadana; Wiwik Susanah Rita; Frida R. Koreh (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2007)
Isolation and identification of antifeedant compounds from brotowali stem (Tinospora tuberculataBEUMEE.) was done. Brotowali dry powder of 1 kg was extracted using methanol by maceration, The methanolextract then was fractionated repeatedly by n-hexane, so that methanol and n-hexane extracts were obtained. Both ofextracts were evaporated by rotary vacuum evaporator, so concentrated methanol and n-hexane extracts wereobtained and then their antifeedant activity was tested. More active extract was separated by thin layerchromatography (TLC) then continued by column chromatography utilizes silica gel 60 as a stationary phase and thebest mobile phases of TLC. Fractions obtained were tested of their antifeedant activity. More active fraction thenwas tested its purity and identified by phytochemical test and UV-vis and infrared spectrophotometer.As much as 97.07 g of concentrated methanol extract was resulted from 1 kg brotowali dry powder.Fractionation of the methanol extract using n-hexane resulted 22.92 g of concentrated methanol and 21.71 g ofconcentrated n-hexane. n-hexane extract points out more activity as antifeedant than methanol extract. The bestmobile phase of TLC was n-hexane: chloroform (1:1 ). The unite result from the column chromatography wasobtained 3 fractions where fraction c points out antifeedant active. The purity test of fraction c was obtained 1 spotso continued by phytochemical test and UV-vis and infrared spectrophotometer. Phytochemical test andspectrophotometry analysis from active isolate (fraction c) point out that the compound included triterpenoid groupthat absorb on wavelength 288.6 nm and 310.6 nm, and be considered having functional group of O-H bonded, CO,C-H, C=O, C=C, and C-H.